Modelling and monitoring of resin transfer moulding - Skordos, Alexandros A. (Cranfield University, 2000)
Modelling and monitoring tools appropriate for the resin transfer moulding composites manufacturing route were developed in this study. A simulation of the curing stage of the process based on a finite elements solution of the non-linear heat conduction equation was implemented. The simulation involved appropriate submodels for the incorporation of thermal properties and cure kinetics. A novel non-parametric procedure which utilises interpolation applied directly to experimental Winefics data proved adequate for the simulation of chemical and structural phenomena occurring during the cure. The application of the heat transfer model was successful, the magnitude of thermal gradients was shown*to be significant and the character of degree of cure gradients temporary. An inversion of the heat transfer simulation based on genetic algorithms enabled an optihisation of the cure process parameters to be performed. The heat transfer simulation was combined with thermal monitoring results in order to achieve an extension of the local temperature measurements to the whole component. This combined scheme reproduced successfully the' temperature and degree of cure distributions. The same approach was implemented with similar outcomes using artificial cure monitoring results. Impedance cure monitoring was used in order to follow in real time the reaction progress. An interpretation was found for the manifestation of vitrification in the impedance signals. A new equivalent circuit representing accurately the behaviour of the resin system investigated was developed. A methodology which correlates the progress of cure with the imaginary impedance spectrum evolution was established. Dielectric flow monitoring techniques appropriate for the filling stage of resin transfer moulding were devised. Lineal sensors enabled monitoring of the progress of filling to be made in both conductive and non-conductive reinforcements.